2021
DOI: 10.1108/jtf-10-2021-0235
|View full text |Cite
|
Sign up to set email alerts
|

I'm afraid to travel! Investigating the effect of perceived health risk on Malaysian travellers' post-pandemic perception and future travel intention

Abstract: PurposeThis study investigates the effect of COVID-19 pandemic perceived health risk on traveller's post-pandemic perception and future travel intention. The study aims to provide insight into the unprecedented COVID-19 pandemic and its potential influence on tourist behaviour.Design/methodology/approachTwo hundred and forty-four responses were gathered quantitatively through an online survey. The research hypotheses were analysed using the partial least square structural equation modelling (PLS-SEM).FindingsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Likewise, the perceived risk associated with COVID-19 has a positive effect on travel evading behavior (Gupta et al, 2021). However, the study found that perceived risk from epidemic negatively affects the tourist's future travel intention (Hanafiah et al, 2021). A recent study found that if the tourist has high perceived risk (Physical risk, equipment risk, cost risk, social risk, performance risk and psychological risk) that negatively affect the travel intention (Jiang et al, 2022), Also study found that risk aversion negatively affects the travel intention (Jiang et al, 2022).…”
Section: Barrier Of Tourist Behaviormentioning
confidence: 82%
See 2 more Smart Citations
“…Likewise, the perceived risk associated with COVID-19 has a positive effect on travel evading behavior (Gupta et al, 2021). However, the study found that perceived risk from epidemic negatively affects the tourist's future travel intention (Hanafiah et al, 2021). A recent study found that if the tourist has high perceived risk (Physical risk, equipment risk, cost risk, social risk, performance risk and psychological risk) that negatively affect the travel intention (Jiang et al, 2022), Also study found that risk aversion negatively affects the travel intention (Jiang et al, 2022).…”
Section: Barrier Of Tourist Behaviormentioning
confidence: 82%
“…We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021). We also noted that three studies were conducted in the USA context (Chua et al, 2020(Chua et al, , 2021Milman et al, 2020;Rasoolimanesh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All constructs were reliable since the reliability values exceed the minimum limit of 0.7 (Hair et al, 2019). The item loadings and AVE statistics of each reflective indicator were higher than the recommended threshold (Hair et al, 2011;Hanafiah et al, 2021), illustrating achieved convergent validity for all variables. To examine discriminant validity, Heterotrait-Monotrait (HTMT) ratio of the correlation was used.…”
Section: Evaluation Of Measurement Modelmentioning
confidence: 87%
“…While this has been an unexcepted winter for the airline industry, special attention should be paid to passengers so that airline companies can adopt different strategies to recover in this unique period. With the decrease of the COVID-19 cases and removal of travel restrictions in 2021, customers’ travel needs revived ( Hanafiah et al, 2021 ). Nevertheless, most travelers still keep vigilant about the healthy precautions ( Matiza & Kruger, 2021 ).…”
Section: Introductionmentioning
confidence: 99%